ANALYSIS OF PROFITABILITY AS A MEDIATING VARIABLE IN THE INFLUENCE OF INVESTMENT DECISION AND DEBT POLICY ON THE COMPANY VALUE OF NON-FINANCIAL AND SERVICE SECTOR FIRMS LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) FOR THE PERIOD 2021-2024: Bahasa Inggris - Mohamad Afrizal Miradji; Wahyu Ari Andrianto; M.Adhi Prasnowo (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
This research examines the impact of profitability, as an intermediary variable, on the correlation between investment choices and debt policies on firm value in the non-financial and service industries listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. Secondary data from the company's annual reports were analyzed using multiple linear regression. The study findings indicate that profitability serves as a crucial mediator in enhancing the company's worth. Investors who base their investment decisions on favorable profitability forecasts and prudent debt management may increase the company's worth. This study underscores the need for effective management strategies to oversee investments and loans to enhance corporate value.